PAJAK KARBON, KERUSAKAN KARBON, DAN PERTUMBUHAN EKONOMI DI LIMA BELAS NEGARA SELAMA 27 TAHUN - Riris Rotua Sitorus; Tangguh Pratysto (Universitas Muhammadiyah Tangerang, 2018)
The purpose of this study is to analyze the effect of carbon tax and carbon damage on economic growth in 15 (fifteen) countries from 1990 to 2017. Based on the results of research by weather scientists who stated that there are 50-500 possibilities to limit global warming at 2 degrees Celsius above average global temperatures from pre-industrial times throughout the 21st century.Global warming is caused by cumulative carbon emissions which continue to increase from year to year, resulting in threats to the world's sustainable development. Therefore carbon production must be limited by imposing a tax on carbon so that economic growth can run normally and even increase.Researchers used the open economy model Y = (C, I, G, NX) namely final household consumption expenditure (C), foreign direct investment (I), government final consumption general expenditure (G), and import export per GDP (NX) for control variables. The researcher also used the Cobb-Douglas Y = (K, L) production function, namely gross capital formation (K) and the ratio of working people per population (L) to the control variable. The data used were panel data in 15 countries that applied Carbon Tax from 1990 to 2017. Researchers used GLS (Generalized Least Squares) estimation to analyze the effect of carbon tax and carbon destruction on economic growth.The result is a carbon tax can stimulate the growth of real gross domestic product per capita and carbon damage hinder economic growth.